ANALISIS PROFIL KESIAPAN KELUARGA DALAM RANGKA MEMFASILITASI PERKEMBANGAN BAHASA ANAK DI RUMAH PADA SAAT PANDEMI (STUDI KUALITATIF KEPADA ORANG TUA SISWA SEKOLAH DASAR) - Labib Sajawandi; Nia Anggri Noveni; Aji Heru Muslim (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2022)
This study aims to determine the readiness of families, especially in parents in facilitating language developmnet at home in pandemic era, and to analyze readiness in a complex manner both of facilities and family culture. This research was conducted on 70 parents or guardians of elementary school students. This study used qualitative research method. Data analysis used the Miles and Huberman models with the following steps; (1) data collection, (2) data reduction, (2) data presentation, and (3) drawing conclusions / verification. Data were collected through observation and interviews. The results of the study were discussed from two aspects of the student language environment, namely the physical and non-physical environments. From these two environments, it can be concluded that there are four principles of literate family, namely 1) The abundance of reading material. 2) Various texts/labeling based on the children's needs. 3) language interaction. 4) Integrated and sustainable activity. From these four principles, it is found that in average, the language interaction in family is high enough only, and this is related to the purpose of formal education. However, the environment and culture of family language have not been built in integrated and sustainable way considering that preparing literate generations in pandemic era must focus on sustainable and integrated processes in order to get long term benefits. So the results of this study are necessary to be used as a reference for parents, schools, and policy makers in preparing schools to study at home.